Characteristics of asymptotic solutions for slightly rounded contacts - Dini,D; Hills,DA (Tribology Materials Surfaces and Interfaces, 2008)
The characteristics of a semi-infinite flat and rounded contact, subject to constant normal load and oscillating shear, are found. These include the slip displacement and frictional energy expenditure, together with the process of frictional shakedown. The set of solutions is applied to the problem of a D shaped punch having a very small radius at the notionally sharp corner. The possible application of the methodology outlined in this paper to a range of fretting fatigueproblems is also discussed. © 2008 W. S. Maney & Son Ltd.